Greening of innovation-technological development of Kazakhstani mining-metallurgical complex - Kabdybay, A.K.; Kenzhebekov, N.D.; Ulybyshev, D.N.; Zhailauov, Ye.B. (KU Publ., 2021)
Object: the aim is to justify and determine the algorithm of actions of greening the production processes of MMC of Kazakhstan as an effective mechanism of technological development and modernization of the industry. Methods: the method of system analysis, the method of secondary information collection, the method of goal structuring were used during the study. Results: comprehensive analysis on formation, accumulation and use directions of man-made mineral formations was given, the main problems of use of man-made mineral formations were identified, the main steps to determine the direction of greening of production processes in the mining-metallurgical industry were determined. Conclusions: a common problem for the entire industry of the mining-metallurgical complex of the republic is the lack of a system for the regular collection and analysis of information on man-made sources of mineral raw materials. Only an approximate quantification of their levels of education can be made in the present. The study of man-made mineral formations will greatly help to create a monitoring system and a database of man-made mineral formations. In order to green the MMC comprehensive geological and technological studies of man-made deposits (mine dumps, tailings of processing plants, slag of metallurgical plants, etc.) should be carried out with an assessment of the quality of useful man-made mineral forms, the extraction of ores that are profitable for mining, and the contouring of productive deposits
Қазақстанның тау-кен металлургия кешенін инновациялық-технологиялық дамытуды экологияландыру
Экологизация инновационно-технологического развития горно-металлургического комплекса Казахстана
Keywords: mining-metallurgical complex; technogenic mineral formations; greening; rational use of mineral resources; technological policy; environmentally safe production